A Perspective on Adventitious Root Formation in Tree Species - Carmen Díaz-Sala (Plants, 2020)
Adventitious root formation is an organogenic process, regulated at several levels, that is crucial for the successful vegetative propagation of numerous plants. In many tree species, recalcitrance to adventitious root formation is a major limitation in the clonal propagation of elite germplasms. Information on the mechanisms underlying the competence for adventitious root formation is still limited. Therefore, increasing our understanding of the mechanisms that enable differentiated somatic cells to switch their fates and develop into root meristematic cells, especially those involved in cell developmental aging and maturation, is a priority in adventitious root-related research. The dynamic cell wall–cytoskeleton, along with soluble factors, such as cellular signals or transcriptional regulators, may be involved in adult cell responses to intrinsic or extrinsic factors, resulting in maintenance, induction of root meristematic cell formation, or entrance into another differentiating pathway.